Flourishing in Darkness: Protist Communities of Water Sites in Shulgan-Tash Cave (Southern Urals, Russia) - Natalia E. Gogoleva; Marina A. Nasyrova; Alexander S. Balkin; Olga Ya. Chervyatsova; Lyudmila Yu. Kuzmina; Elena I. Shagimardanova; Yuri V. Gogolev; Andrey O. Plotnikov (Diversity)
Karst caves, formed by the erosion of soluble carbonate rocks, provide unique ecosystems characterized by stable temperatures and high humidity. These conditions support diverse microbial communities, including wall microbial fouling, aquatic biofilms, and planktonic communities. This study discloses the taxonomic diversity of protists in aquatic biotopes of Shulgan-Tash Cave, a culturally significant site and popular tourist destination, by 18S rRNA gene metabarcoding. Our findings reveal the rich protist communities in the cave’s aquatic biotopes, with the highest diversity observed in Blue Lake at the cave entrance. In contrast, Distant Lake in the depth of the cave was inhabited by specific communities of plankton, mats, and pool fingers, which exhibited lower richness and evenness, and were adapted to extreme conditions (cold, darkness, and limited nutrients). High-rank taxa including Opisthokonta, Stramenopiles, and Rhizaria dominated all biotopes, aligning with observations from other subterranean environments. Specific communities of biotopes inside the cave featured distinct dominant taxa: amoeboid stramenopile (Synchromophyceae) and flagellates (Choanoflagellatea and Sandona) in mats; flagellates (Choanoflagellatea, Bicoecaceae, Ancyromonadida) and amoeboid protists (Filasterea) in pool fingers; flagellates (Ochromonadales, Glissomonadida, Synchromophyceae), fungi-like protists (Peronosporomycetes), and fungi (Ustilaginomycotina) in plankton. The specificity of the communities was supported by LEfSe analysis, which revealed enriched or differentially abundant protist taxa in each type of biotope. The predominance of Choanoflagellatea in the communities of cave mats and pool fingers, as well as the predominance of Synchromophyceae in the cave mats, appears to be a unique feature of Shulgan-Tash Cave. The cold-tolerant yeast Malassezia recorded in other caves was present in both plankton and biofilm communities, suggesting its resilience to low temperatures. However, no potentially harmful fungi were detected, positioning this research as a baseline for future monitoring. Our results emphasize the need for ongoing surveillance and conservation efforts to protect the fragile ecosystems of Shulgan-Tash Cave from human-induced disturbances and microbial invasions.